Image conditions for polar and cylindrical coordinate separation-of-variables acoustic multiple scattering models with perfectly reflecting flat boundaries. Issue 3 (28th March 2018) - Shin, Ho-Chul
Summary: This article addresses efficient implementation of the method of images for acoustic multiple scattering models (MSM) with perfectly reflecting flat boundaries. Time-harmonic problems are first solved in the polar coordinate system for circular scatterers; then the models are extended to the cylindrical coordinate system with (semi-)infinitely long circular cylinders. The MSM in this article is based on the method of separation of variables and Graf's addition theorem. Derivations are provided for 'image conditions' which relate the unknown coefficients of outgoing waves from image scatterers with those of real counterparts. The method of images is applied to wedge-shaped domains with apex angles of $π/n$ rad for a positive integer $n$ . Image conditions make the MSM numerically more efficient: the system of linear equations for unknown coefficients is formulated $2n$ times faster; its memory requirements are reduced by $4n^2$ times for direct solvers. The proposed model is applied to a benchmark wedge in ocean environment with $n=64$ . Good agreement is observed between the MSM with image conditions and the boundary element method. Furthermore, half- and quarter-space measurements in an anechoic chamber are in accordance with the correct use of image conditions. Incorrect image conditions reported elsewhere for polar coordinates are also discussed.